Abonamiento con dosis de gallinaza y distanciamientos de siembra y su influencia en las características agronómicas y rendimiento de Allium fistulosum L. “cebolla china”, en Zungarococha-Loreto. 2021 - Pezo Saldaña, Rice Segundo (2022)
The experiment took place in the facilities of the Teaching and Research Workshop on Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located at Km 4 of the road to Zungarococha, south of the city of Iquitos. The research was experimental, explanatory, prospective with two independent variables (dose of chicken manure and planting spacing) and eleven dependent variables (plant height, number of leaves/plant, root length, root weight, neck diameter of the plant, diameter of the bulb, number of bulbs/plant, weight of bulb/plant, weight of leaves/plant, total weight of the plant and weight of the plants/ha The general objective of the Thesis was to determine if the fertilization with chicken manure dose and planting spacing, influence the agronomic characteristics and yield of Allium fistulosum L. "Chinese onion", in Zungarococha-Loreto, 2021. On average of four repetitions and two planting spacings, statistical significance was found in its effects between the four doses of chicken manure in their effects on plant height, number of leaves per plant, root length, root weight, diameter of the plant neck, bulb diameter, number of bulb bos/plant, weight of bulbs and weight of leaves per plant, highlighting the dose of chicken manure D4 (60 t/ha). On average of four repetitions and four doses of chicken manure, statistical significance was found in its effects between the two planting distances in plant height, the number of leaves per plant, root length and root weight per plant, respectively, standing out in all cases, the distance D2 (0.40 x 0.30 m). Treatment T8 (60 t of chicken manure/ha and 0.40 m x 0.30 m spacing) presented the best leaf weight yield/ha, with 5,900 Kg/ha and the best economic benefit with S/.18,108.00